THE USE OF ANIMATION MOVIE TO IMPROVE STUDENTS’ MOTIVATION IN LEARNING ENGLISH - Dewi Lestari; Dina Irmayanti Harahap (Universitas Potensi Utama, 2021)
This research was conducted by using descriptive qualitative design to the eleventh grade students of SMK Harapan Mekar 2 Medan. The sample of this study was 27 students. The instruments used to collect the data are observation, interview, and questionnaires. The results of interview and observations are the lack of student motivation to learn English because they think English is difficult and boring. However, after the animation movie was applied, students' motivation to learn English was increased and they were enthusiastic in learning. Based on the results of the questionnaires, the researcher concluded that the motivation of eleventh grade students of SMK Harapan Mekar 2 Medan in learning English by using animation movie was at the 'reasonable' level who with an average student score of 73%. The data showed that only one student has an 'Extraordinary' motivation with a score of 88, eight students have a 'Good' score of 78-88, seventeen students have a 'fair' score of 64-75, and one student has a 'bad' score with a score of 61. Based on the results of the questionnaires, the students responses in learning English by using animation movie is very positive.